Clinical Profile and Nursing Diagnosis of the Newborn in a Special Care Nursery (SCN) Unit - Defi Efendi; Yeni Rustina; Dian Sari (Jurnal Ners, 2021)
Introduction: A good comprehension of the clinical profile and nursing diagnosis of newborn in Special Care Nursery (SCN) unit guides decision-making by nurses. In addition, it can become an initial basis for making plans for improving quality of care, management and nursing research. The purpose of this study was to identify clinical profile and nursing diagnosis of newborns in an SCN unit.Methods: It is a quantitative, cross-sectional, descriptive study in SCN (Level II and III) with a sample of 77 medical records of newborns less than 31 days old in a national referral hospital. Descriptive analysis was used to identify demographic characteristic, the medical diagnosis and nursing diagnosis of newborns at birth and hospitalization.Results: Newborns treated in SCN unit are dominated by preterm with low birth weight (74%). Respiratory system disorders (55.8%) and infections (35.1%) dominate newborn problems both at birth or coming. Most   nursing diagnoses when the baby is born or coming are the risk of infection (90.9%) and ineffective breathing patterns (76.6%). As for the treatment, most diagnoses show the risk of infection and hypovolemia.Conclusion: A good clinical profile and nursing diagnosis of newborns can guide nurses to decision-making. Continuous update on nursing diagnosis determination, improvement of nurses’ knowledge about the signs of deterioration, and future research that prioritizes issues in neonates are required to optimize nurses’ role in SCN units.